Validation Of Sgrq-Cm, Risk Factors Of Lung Functions Deterioration And Economic Evaluation In Patients With Chronic Obstructive Pulmonary Disease - Rehman, Anees Ur (2020)
Health status and FEV1 decline are two important factors of the GOLD (Global initiative for chronic Obstructive Lung Disease) multidimensional assessment system. This approach uses symptoms based on health status assessment tools, degree of airflow limitation (FEV1) and risk based on exacerbation frequency to classify patients according to disease severity into four groups GOLD A to D and propose optimum pharmacotherapy. Worsening of health status (increase in symptoms load), decline in FEV1 or increase in exacerbation frequency can result in progression of disease from lower to higher group. COPD is also associated with considerable economic burden on the individual and society. Thus, objectives of the current study were to assess the economic burden of COPD, validate the Malaysian version of St George's Respiratory COPD specific questionnaire (SGRQ-CM) as health status assessment tool and find the risk factors of FEV1 decline in COPD patients. This was a longitudinal prospective cohort including 367 COPD patients from Penang Hospital. Validity, reliability, responsiveness and MCID (minimum clinical important difference) of the of the Malaysian version of SGRQ-C was assessed to be used in population of Malaysia. Univariate and multivariate Cox regression with robust variance were performed to estimate relative risk (RR) for different factors on decline in FEV1 after one year of follow up. Activity-Based Costing, bottom-up approach was used to calculate direct cost, while, indirect costs of the patients were assessed using the Work Productivity and Activity Impairment Questionnaire.